2022
DOI: 10.3390/ijms23052761
|View full text |Cite
|
Sign up to set email alerts
|

The EPH/Ephrin System in Colorectal Cancer

Abstract: The EPH/ephrin system constitutes a bidirectional signaling pathway comprised of a family of tyrosine kinase receptors in tandem with their plasma membrane-bound ligand (ephrins). Its significance in a wide variety of physiologic and pathologic processes has been recognized during the past decades. In carcinogenesis, EPH/ephrins coordinate a wide spectrum of pathologic processes, such as angiogenesis, vessel infiltration, and metastasis. Despite the recent advances in colorectal cancer (CRC) diagnosis and trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…It’s contribution in GIST progression has been reviewed[ 56 ] but data about potential effects in GIST vascularization process are missing. Towards the same direction, the Eph/ephrin system has been investigated in carcinogenesis[ 57 , 58 ]. It would be of paramount importance an attempt to outline its contribution in GIST angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It’s contribution in GIST progression has been reviewed[ 56 ] but data about potential effects in GIST vascularization process are missing. Towards the same direction, the Eph/ephrin system has been investigated in carcinogenesis[ 57 , 58 ]. It would be of paramount importance an attempt to outline its contribution in GIST angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…The Eph receptors, with their ligands the Ephrins, are a large family of transmembrane proteins that were originally implicated in many neurological functions [ 173 , 174 ]. Eph/ephrin signaling is exceptionally complicated because of its bidirectional nature (with Ephs and ephrins interacting “in trans” from two different cells), and as a consequence Eph/ephrin have been shown to coordinate a plethora of tumor-related processes from angiogenesis, inflammation, vascular infiltration, and metastasis to tumor immunity [ 175 , 176 , 177 ]. To name a few examples, increased Eph/ephrin signaling is associated with tumor progression in melanoma [ 178 ], breast [ 179 ], prostate [ 180 ], and colorectal cancer [ 175 ].…”
Section: Molecules With a Widespread Activity In Various Types Of Can...mentioning
confidence: 99%
“…Eph/ephrin signaling is exceptionally complicated because of its bidirectional nature (with Ephs and ephrins interacting “in trans” from two different cells), and as a consequence Eph/ephrin have been shown to coordinate a plethora of tumor-related processes from angiogenesis, inflammation, vascular infiltration, and metastasis to tumor immunity [ 175 , 176 , 177 ]. To name a few examples, increased Eph/ephrin signaling is associated with tumor progression in melanoma [ 178 ], breast [ 179 ], prostate [ 180 ], and colorectal cancer [ 175 ]. The Eph family member EPHA2 has recently been proposed as a negative prognostic factor in triple-negative breast cancer (TNBC) patients; moreover, EPHA2 may act as a precision therapeutic target for this challenging condition [ 181 ].…”
Section: Molecules With a Widespread Activity In Various Types Of Can...mentioning
confidence: 99%
“…Substantial evidence indicates that ephrins play a vital role in tumor angiogenesis, invasion, metastasis, and tumor stemness maintenance ( Lodola et al, 2017 ). Many ephrin ligands have been shown to be upregulated in multiple tumors and associated with poor prognosis, such as lung adenocarcinoma ( Deng et al, 2021 ), breast cancer ( Kaenel et al, 2012 ), colorectal cancer ( Papadakos et al, 2022 ), prostate cancer ( Zhao et al, 2021 ), bladder cancer ( Mencucci et al, 2020 ), and other cancers ( Surawska et al, 2004 ). Lin et al (2021) reported that EFNA4 is highly expressed in cancer tissues and leads to poor prognosis in patients with HCC.…”
Section: Introductionmentioning
confidence: 99%